NCMP-10. DYSGRAPHIA AS THE EARLIEST PRESENTING SYMPTOM OF SEVERE CHIMERIC ANTIGEN RECEPTOR (CAR) T-CELL THERAPY NEUROTOXICITY: A SINGLE CENTER EXPERIENCE. (12th November 2021) - Yuen, Carlen; Rezania, Kourosh; Kelly, Thomas; Bishop, Michael
Abstract: INTRODUCTION: Chimeric antigen receptor (CAR) T-cell therapy, including axicabtagene ciloleucel (axi-cel; Yescarta®) and tisagenlecleucel (tisa-cel; Kymriah®), are FDA approved for the treatment of adult patients with relapsed or refractory (R/R) diffuse large B-cell lymphoma (DLBCL). Neurotoxicity (NT) associated with CAR T-cell therapy (immune effector cell-associated neurotoxicity syndrome [ICANS]) can be fatal. Timely data, in the form of an abbreviated bedside mini-mental status exam, is thought to lead to earlier identification of NT. However, existing literature validating this method is limited. MATERIALS AND METHODS: In this retrospective study, patients with R/R DLBCL treated with commercial axi-cel or tisa-cel in our center from December 2017 to September 2018 were assessed for NT with the CTCAE v4 criteria and the CAR-T-cell-therapy-associated TOXicity (CARTOX-10) scoring system. RESULTS: Twenty-six patients with R/R DLBCL were treated with CAR T-cell therapy (25 axi-cel/[Yescarta®] and 1 tisagenlecleucel [Kymriah®]). Twenty-three (88%) developed NT with 8 (31%) experiencing severe NT (Grade III-IV). Tremor and dysgraphia occurred in all patients with severe NT. Lower average CARTOX-10 score (p=< 0.01), dysgraphia (p< 0.01), inattention (p=.018), and disorientation (p=.01) were significantly associated in patients with severe NT. A trend towards significance was observed between tremor and severe NT (p=.08). All patients with severe NT had both dysgraphia and tremor 8/8 (100%) and 2/8 (25%) had concurrent dysnomia. Death occurred in 12/26 (46%) of patients due to disease progression (n=11) and cardiac failure due to myositis (n=1). CONCLUSION: In our limited cohort, dysgraphia, inattention, and disorientation are heralding symptoms of severe NT in adult R/R DLBCL patients treated with commercial CAR T-cell therapy. Dysgraphia was the earliest presenting symptom in patients with severe CAR T-cell neurotoxicity and was likely a manifestation of motor dysfunction rather than a component of dysphasia. Further studies with a larger cohort are needed to validate our findings.